A hydrocracking method for producing more naphtha from diesel
By using a special hydrogenation catalyst during the hydrocracking process, diesel is converted into naphtha, and the problem of low naphtha yield in the existing technology is solved, and high-efficiency production of high-frying naphtha is achieved.
Patent Information
- Application Number
- CN202111256519.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-10-27
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2041-10-27
AI Technical Summary
In the process of producing naphtha from diesel raw materials, the yield is relatively low, making it difficult to meet the market demand for Gaofang Qian naphtha.
Using the hydrocracking method, under hydrogenation conditions, paraffin-based or paraffin-based diesel and hydrogen are contacted with a special hydrogenation catalyst in a fixed bed hydrogenation reactor. The composition and structure of the catalyst are optimized by using nickel and tungsten as active metal components, combining non-amorphous mesoporous acidic materials and Y-type molecular sieve support.
It significantly improves the yield and selectivity of naphtha, increases the yield of high aromatic heavy naphtha, and improves the temperature distribution of the cracking reactor and improves the stability of the device operation.
Abstract
Description
Technical Field
[0001] The invention relates to the field of oil refining and chemical industry, in particular to the field of heavy raw material processing, and more particularly to a hydrocracking method for producing more naphtha from diesel. Background Art
[0002] With the improvement of energy conservation, emission reduction and environmental protection requirements, the pace of diesel quality upgrade is accelerating. At the same time, due to the slowdown in economic growth, the apparent consumption of diesel has decreased year by year, and the trend of diesel surplus is obvious. Refining companies are facing the contradiction between increasing costs to produce high-quality diesel products and the continuous decline in prices caused by excess diesel resources, and the business environment of enterprises has deteriorated significantly. Therefore, it is imperative to improve corporate benefits by optimizing product structure.
[0003] At the same time, the current growth rate of the aromatics market has led to an increasing demand for high aromatic potential naphtha as a reforming feedstock. Converting diesel fractions into naphtha fractions is an important way to increase technical added value.
[0004] There are two main types of hydrocracking technologies for producing more naphtha. One is to use diesel fractions as raw materials to produce more naphtha fractions, and the other is to use heavy fractions such as VGO (vacuum gas oil), coker gas oil, deasphalted oil and coal-derived oil.
[0005] The inventions using diesel fraction as raw material include:
[0006] Chinese patent document CN201610178572.8 proposes a method for producing naphtha and clean gasoline from catalytic cracking diesel, comprising: mixing catalytic cracking diesel with hydrogen and entering the middle part of a reverse-sequence hydrocracking reactor-hydrofining reactor, mixing with the cracking product from the hydrocracking reactor and entering the hydrofining reactor for hydrofining reaction to remove impurities such as sulfur and nitrogen, and perform olefin saturation reaction and aromatic hydrogenation saturation; cutting the product after hydrofining, using the distillate oil less than 165°C as a naphtha product as a raw material for a catalytic reforming unit; using the distillate oil of 165-205°C as a clean gasoline blending component; returning the distillate oil of 205-320°C to the top of the reverse-sequence hydrocracking reactor-hydrofining reactor for hydrocracking and hydrofining reactions; and returning the distillate oil of more than 320°C to the catalytic cracking unit for further cracking or entering other hydrogenation units for processing. The method of the present invention aims to produce more naphtha products and can also produce clean gasoline. The commercial brand of the hydrorefining catalyst matched with the patent is THDS-I, and the commercial brand of the hydrocracking catalyst is THHC-II, which are developed and produced by CNOOC Tianjin Chemical Research and Design Institute. Chinese patent CN105694966A has similar characteristics.
[0007] Chinese patent document CN111100697A proposes a hydrocracking method for paraffin-based diesel, comprising the following contents: (1) paraffin-based diesel feedstock is mixed with hydrogen and enters a hydrotreating reactor for desulfurization, denitrogenation and aromatic saturation reaction; (2) the effluent of step (1) enters a hydrocracking reactor, and the mass content of Y molecular sieve in the hydrocracking catalyst loaded in the hydrocracking reactor presents a high-low-high trend along the logistics direction; (3) the effluent of the hydrocracking reactor is subjected to gas-liquid separation and liquid phase fractionation to obtain naphtha, jet fuel and diesel. This method increases the production of heavy naphtha with high aromatic potential while improving the temperature distribution of each bed of the cracking reactor and improving the stability of the device operation. The matching hydrotreating catalyst is the commercially available FF-56 catalyst, and the hydrocracking catalyst I, hydrocracking catalyst II and hydrocracking catalyst III are commercially available products.
[0008] The inventions related to the production of naphtha from heavy fractions such as VGO (vacuum gas oil), coker gas oil, deasphalted oil and coal-derived oil include:
[0009] Chinese patent document CN107987879A proposes a hydrocracking method for producing heavy naphtha and tail oil, which comprises: in the presence of hydrogen, reacting the raw oil through a hydrofining reactor and a hydrocracking reactor in sequence to obtain a hydrocracking effluent; then introducing the hydrocracking effluent into a separation device for gas-liquid separation and fractionation in sequence to obtain a light naphtha fraction, a heavy naphtha fraction, a kerosene fraction, a diesel fraction and a tail oil fraction; introducing at least part of the kerosene fraction and / or at least part of the diesel fraction into the first catalyst bed of the hydrocracking reactor for circulation. The method of the present invention is simple, has low energy consumption and hydrogen consumption, and can produce high-quality tail oil and heavy naphtha products. The raw oil used in the invention is at least one of vacuum wax oil, coking wax oil, deasphalted oil and coal-made oil.
[0010] Chinese patent document CN110835551A proposes a hydrocracking method, which includes: (1) introducing a VGO fraction into a high-pressure reaction zone for a first hydrogenation reaction to obtain an effluent I; (2) introducing raw diesel and the effluent I into a low-pressure reaction zone for a second hydrogenation reaction to obtain an effluent II; (3) fractionating the effluent II; wherein the hydrogen partial pressure in the low-pressure reaction zone is 20 to 80% of the hydrogen partial pressure in the high-pressure reaction zone. The method provided by the present invention can greatly increase the heavy naphtha yield of the hydrocracking unit, while also taking into account the production of high-quality tail oil. The raw materials used in the invention are mainly VGO fractions.
[0011] Chinese patent document CN105817259A (application terminated on October 9, 2018) proposes a high-yield naphtha-type hydrocracking catalyst and a preparation method thereof, wherein the hydrocracking catalyst is composed of a hydrogenation active metal and a carrier containing a modified Y molecular sieve, amorphous silicon aluminum and alumina powder; wherein the physicochemical properties of the modified Y molecular sieve are as follows: the average grain diameter is 150-650nm, the framework SiO2 / Al2O3 molar ratio is 10.0-25.0, the sodium oxide content is <0.05wt%, the unit cell parameter is 2.434-2.445nm, the relative crystallinity is 95-125%, the pyridine-infrared acid content is 0.60-1.2mmol / g, the medium-strong B acid content accounts for 75-85% of the total acid content, the specific surface area is 550-850m2 / g, and the pore volume is 0.40-0.85mL / g. The invention adopts the ammonium salt inorganic acid-rare earth organic acid coupling modification Y modification technology and active metal positioning control technology to comprehensively match the cracking activity and hydrogenation active center, and improve the catalyst's conversion of macromolecular components in the raw material and the selectivity of naphtha. The raw materials applicable to this invention are mainly VGO.
[0012] Chinese patent document CN102463131B proposes a hydrocracking catalyst and a preparation method thereof, wherein the aluminum hydroxide dry glue powder used in the carrier is first impregnated with a solution containing a hydrogenation metal component, and then the catalyst is obtained by fully rolling, molding and roasting together with a molecular sieve under the action of a peptizing agent or a binder after drying. The catalyst product can be obtained by high-temperature roasting the catalyst of the present invention only once, the preparation method is simple, and the preparation cost is significantly reduced. In addition, the hydrogenation center and the cracking center of the catalyst of the present invention are coordinated and have high catalytic activity, and at the same time have a large specific surface area and pore volume, which is more suitable for the catalytic process of producing more naphtha by hydrocracking of high-drying point and inferior vacuum distillate oil.
[0013] Chinese patent document CN105709798A proposes a hydrocracking catalyst and a preparation method thereof. The hydrocracking catalyst of the invention adopts a Y-type molecular sieve with large grains and concentrated effective pore size distribution as an acidic component, which is suitable as a hydrocracking catalyst for increasing the production of high-quality heavy naphtha and has high catalytic activity and selectivity. Summary of the invention
[0014] The object of the present invention is to further improve the yield of naphtha produced from diesel feedstock.
[0015] In order to achieve the above object, the present invention provides a method for hydrocracking diesel to produce naphtha, wherein diesel and hydrogen are contacted with a hydrogenation catalyst in a fixed bed hydrogenation reactor under hydrogenation conditions; the diesel is a paraffinic or paraffinic diesel fraction;
[0016] Wherein, the hydrogenation catalyst comprises a carrier and an active metal component supported on the carrier;
[0017] The active metal components are nickel and tungsten; the nickel content is 0.5-10% by weight and the tungsten content is 8-30% by weight based on the total amount of the catalyst and calculated as oxide;
[0018] Based on the total mass of the hydrogenation catalyst, the content of the carrier is 60-90% by weight;
[0019] The carrier contains a non-amorphous mesoporous acidic material and a Y-type molecular sieve; based on the total mass of the carrier, the content of the Y-type molecular sieve is 0.5-20% by weight.
[0020] Optionally, the initial distillation point of the diesel is 100-300°C, preferably 180-240°C; the final distillation point is 330-450°C, preferably 370-400°C; the coking diesel fraction in the diesel is within 10% by weight; the aromatic content is not higher than 20%, the nitrogen content is not higher than 500 μg / g, the density is not greater than 0.88 g / mL; and the cetane index is not less than 40.
[0021] Optionally, the nickel content based on the total amount of the catalyst and calculated as oxide is 1-8% by weight, preferably 2-8% by weight; the tungsten content is 12-32% by weight, preferably 20-28% by weight.
[0022] Optionally, based on the total mass of the hydrogenation catalyst, the content of the carrier is 65-85% by weight; based on the total mass of the carrier, the content of the Y-type molecular sieve is 1.5-10% by weight, preferably 4-10% by weight, and further preferably 6-10% by weight; the unit cell constant of the Y-type molecular sieve is in the range of 2.42-2.465 nm; preferably 2.430-2.460 nm.
[0023] Optionally, the carrier has a porous structure; in the porous structure, the pores have a pore size in the range of 4-12 nm, preferably in the range of 5-9 nm; the pores with a pore size in the range of 3-50 nm account for more than 30% of the total pore volume; the specific surface area of the carrier is 200-450 m 2 / g, preferably 220-420m 2 / g; the pore volume of the carrier is 0.35-0.80mL / g, preferably 0.40-0.75mL / g; the pore concentration value of the pores is not less than 0.5, preferably not less than 0.75.
[0024] Optionally, the non-amorphous mesoporous acidic material is a silicon-aluminum composite oxide; in the non-amorphous mesoporous acidic material, the content of sodium oxide is less than 0.1%, preferably the content of sodium oxide is less than 0.01wt%, further preferably less than 0.008wt%, more preferably less than 0.005wt%; the content of silicon oxide ranges from 1-75 wt%, preferably 5-60 wt%, more preferably 10-50 wt%.
[0025] Optionally, the hydrogenation catalyst is prepared according to the following steps:
[0026] S1, mixing pseudo-thin aluminum water stone, amorphous silicon aluminum oxide, Y-type molecular sieve and sesbania powder to obtain a first mixed powder; mixing the first mixed powder with a nitric acid solution, kneading and extruding to obtain an extruded strip; performing a first drying and a first calcination on the extruded strip to obtain a carrier;
[0027] S2, impregnating the support with an aqueous solution of a compound containing a nickel element and a compound containing a tungsten element to obtain an impregnated support;
[0028] S3, subjecting the impregnated support to a second drying and a second calcination.
[0029] Optionally, the compound containing nickel element is selected from at least one of nickel nitrate, nickel sulfate, nickel acetate, basic nickel carbonate and nickel chloride; the compound containing tungsten element is selected from at least one of tungstic acid, metatungstic acid, ethyl metatungstic acid, tungstate, metatungstate and ethyl metatungstic acid.
[0030] Optionally, in step S1, the mixing conditions include: temperature of 10-40°C, time of 1-10 minutes; the first drying conditions include: temperature of 80-350°C, preferably 100-300°C; time of 0.5-24 hours, preferably 1-12 hours; the first calcining conditions include: temperature of 360-700°C, preferably 400-650°C; time of 0.2-12 hours, preferably 1-10 hours; air flow of 20-50 L / h; In step S2, the conditions for the impregnation include: an impregnation temperature of 5-150°C and an impregnation time of 0.5-12 hours; in step S3, the conditions for the second drying treatment include: a drying temperature of 50-300°C, preferably 105-250°C; a drying time of 1-24 hours, preferably 2-12 hours; the conditions for the second roasting include: a roasting temperature of 350-600°C, preferably 400-550°C; and a roasting time of 1-10 hours, preferably 2-8 hours.
[0031] Optionally, in step S1, the weight ratio of the pseudo-thin diatomite, the amorphous silicon aluminum oxide, the Y-type molecular sieve and the sesbania powder is 10-80:20-85:1-20:1-5; preferably 15-75:25-80:2-15:2-4; the amount of the nitric acid solution is 0.3-2.5 mL for every 100 g of the mixed powder; the SiO 2 The content of Fe is less than 0.1wt%, 2 O 3 The content is less than 0.01wt%, Na 2 The content of O is less than 0.15wt%, the content of water is less than 3wt%, and the loss on ignition is 32-38%; the pore volume of the pseudo-thin alumina is 0.60-1.1mL / g, and the specific surface area is 220-310m 2 / g; the characteristics of the amorphous silicon aluminum oxide include: SiO 2 The content is 15-55%, Al 2 O 3 The content is 45-85%, and the bulk density is 250-450g / L; the mass concentration of the nitric acid solution is: 0.5-2.5%.
[0032] Optionally, the hydrogenation conditions include: temperature of 300-420°C, preferably 350-400°C; hydrogen partial pressure of 3.5-20.0 MPa, preferably 5.0-15.0 MPa; liquid hourly volume space velocity of the raw material of 0.1-5h -1 , preferably 0.3-3.0h -1 .
[0033] Through the above technical scheme, the present invention uses diesel fraction as raw material and adopts a hydrocracking method to maximize the production of naphtha.
[0034] Other features and advantages of the present invention will be described in detail in the following detailed description. DETAILED DESCRIPTION
[0035] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.
[0036] The present invention provides a method for hydrocracking diesel to produce naphtha, wherein diesel and hydrogen are contacted with a hydrogenation catalyst in a fixed bed hydrogenation reactor under hydrogenation conditions; the diesel is a paraffin-based or paraffin-based diesel fraction;
[0037] Wherein, the hydrogenation catalyst comprises a carrier and an active metal component supported on the carrier;
[0038] The active metal components are nickel and tungsten; the nickel content is 0.5-10% by weight and the tungsten content is 8-30% by weight based on the total amount of the catalyst and calculated as oxide;
[0039] Based on the total mass of the hydrogenation catalyst, the content of the carrier is 60-90% by weight;
[0040] The carrier contains a non-amorphous mesoporous acidic material and a Y-type molecular sieve; based on the total mass of the carrier, the content of the Y-type molecular sieve is 0.5-20% by weight.
[0041] The hydrocracking method mentioned in the present invention is one of the petroleum refining processes. It is a process in which heavy oil undergoes cracking reaction under the conditions of heating, high hydrogen pressure and the presence of a catalyst to convert it into gas, gasoline, jet fuel, diesel, etc. The hydrocracking raw material is usually a heavy distillate oil obtained by crude oil distillation, including light deasphalted oil after solvent deasphalting of vacuum residue. Its main feature is that the production flexibility is large, and the product yield can be controlled by different operating conditions, or mainly for the production of gasoline, or mainly for the production of low freezing point jet fuel, low freezing point diesel, or for the production of lubricating oil raw materials.
[0042] The naphtha mentioned in the present invention is one of the petroleum products, also known as chemical light oil. It is a light oil used as a chemical raw material produced by processing crude oil or other raw materials, and is mainly used as a reforming and chemical raw material. There are various distillation ranges due to different uses. China stipulates that the distillation range is from the initial distillation point to about 220°C. When used as a cracking raw material for producing ethylene, a 70-145°C fraction is used, which is called light naphtha; when the purpose is to produce aromatics or high-octane gasoline, a 70-180°C fraction is used, which is called heavy naphtha; when used as a solvent, it is called solvent naphtha; aromatic solvents from coal tar are also called heavy naphtha or solvent naphtha.
[0043] The non-amorphous mesoporous acidic material mentioned in the present invention generally adopts a two-component oxide, such as aluminum oxide-silicon oxide, aluminum oxide-titanium oxide, aluminum oxide-magnesium oxide, silicon oxide-magnesium oxide, silicon oxide-zirconium oxide, silicon oxide-thoria oxide, silicon oxide-beryllium oxide, silicon oxide-titanium oxide, titanium oxide-zirconium oxide, etc. A third component can be added on the basis of the two components, and there is no restriction on the added third component. More components can be added on the basis of the two components or three components, and there is no restriction on the added components.
[0044] The non-amorphous mesoporous acidic material mentioned in the present invention is preferably a silicon-aluminum composite oxide, a titanium-aluminum composite oxide, or a titanium-silicon composite oxide, among which a silicon-aluminum composite oxide is more preferred.
[0045] As a preferred embodiment of the present invention, the initial distillation point of the diesel is 100-300°C, preferably 180-240°C; the final distillation point is 330-450°C, preferably 370-400°C; the coking diesel fraction in the diesel is within 10% by weight; the aromatic content is not higher than 20%, the nitrogen content is not higher than 500 μg / g, the density is not greater than 0.88 g / mL; and the cetane index is not less than 40.
[0046] According to the present invention, the nickel content in terms of oxide based on the total amount of the catalyst may be 1-8% by weight, preferably 2-8% by weight; the tungsten content may be 12-32% by weight, preferably 20-28% by weight.
[0047] According to the present invention, based on the total mass of the hydrogenation catalyst, the content of the carrier can be 65-85% by weight; based on the total mass of the carrier, the content of the Y-type molecular sieve can be 1.5-10% by weight, preferably 4-10% by weight, and further preferably 6-10% by weight; the unit cell constant of the Y-type molecular sieve can range from 2.42-2.465nm; preferably 2.430-2.460nm.
[0048] Preferably, the carrier may have a porous structure; in the porous structure, the pores may have a pore size in the range of 4-12 nm, preferably in the range of 5-9 nm; the pores with a pore size in the range of 3-50 nm account for more than 30% of the total pore volume; the specific surface area of the carrier may be 200-450 m 2 / g, preferably 220-420m 2 / g; the pore volume of the carrier is 0.35-0.80mL / g, preferably 0.40-0.75mL / g; the pore concentration value of the pores is not less than 0.5, preferably not less than 0.75.
[0049] According to the present invention, the non-amorphous mesoporous acidic material may be a silicon-aluminum composite oxide; in the non-amorphous mesoporous acidic material, the content of sodium oxide may be lower than 0.1%, preferably the content of sodium oxide is lower than 0.01wt%, further preferably lower than 0.008wt%, more preferably lower than 0.005wt%; the content of silicon oxide may range from 1-75 wt%, preferably 5-60 wt%, more preferably 10-50 wt%.
[0050] According to the present invention, the hydrogenation catalyst can be prepared according to the following steps:
[0051] S1, mixing pseudo-thin aluminum water stone, amorphous silicon aluminum oxide, Y-type molecular sieve and sesbania powder to obtain a first mixed powder; mixing the first mixed powder with a nitric acid solution, kneading and extruding to obtain an extruded strip; performing a first drying and a first calcination on the extruded strip to obtain a carrier;
[0052] S2, impregnating the support with an aqueous solution of a compound containing a nickel element and a compound containing a tungsten element to obtain an impregnated support;
[0053] S3, subjecting the impregnated support to a second drying and a second calcination.
[0054] According to the present invention, the compound containing nickel element can be selected from at least one of nickel nitrate, nickel sulfate, nickel acetate, basic nickel carbonate and nickel chloride; the compound containing tungsten element can be selected from at least one of tungstic acid, metatungstic acid, ethyl metatungstic acid, tungstate, metatungstate and ethyl metatungstic acid.
[0055] According to the present invention, in step S1, the mixing conditions may include: temperature of 10-40°C, time of 1-10 minutes; the first drying conditions may include: temperature of 80-350°C, preferably 100-300°C; time of 0.5-24 hours, preferably 1-12 hours; the first roasting conditions may include: temperature of 360-700°C, preferably 400-650°C; time of 0.2-12 hours, preferably 1-10 hours; air flow rate of 20-50L / h.
[0056] The method of the present invention can add an appropriate amount of extrusion aid and / or adhesive during extrusion molding, and then extrusion molding. The type and amount of the extrusion aid and peptizing agent have a relatively large impact on the pore concentration. Selecting an appropriate extrusion aid can improve the pore concentration of the carrier. The types of extrusion aids include, but are not limited to, organic carboxylic acids, polyols, organic amines, surfactants, etc. The organic carboxylic acid refers to a compound with a carboxyl group, including but not limited to: formic acid, acetic acid, oxalic acid, propionic acid, malonic acid, butyric acid, succinic acid, glutaric acid, adipic acid, benzoic acid, phthalic acid, phenylpropionic acid, etc., and other unlisted ones can be found in the second edition of "Lan's Handbook of Chemistry", 1.26-1.27. The surfactant refers to a substance with fixed hydrophilic and lipophilic groups, which can be arranged in a directional manner on the surface of the solution and can significantly reduce the surface tension. These include: 1. Anionic surfactants, such as stearic acid, sodium dodecylbenzene sulfonate, etc.; 2. Cationic surfactants, such as quaternary ammonium compounds, etc.; 3. Zwitterionic surfactants, such as lecithin, amino acid type, betaine type, etc.; 4. Nonionic surfactants, such as fatty acid glycerides, polyols, including fatty acid sorbitan (Span), polysorbate (Tween), polyoxyethylene type and polyoxyethylene-polyoxypropylene copolymers, etc. The polyols refer to compounds containing multiple OH groups in the molecular structure, including but not limited to ethylene glycol, propylene glycol, butanediol, etc. The organic amines refer to: monoethanolamine, diethanolamine, triethanolamine, N-methyldiethanolamine, urea, etc.
[0057] In step S2, the method of contacting the aqueous solution of the compound containing the hydrogenation active component with the catalyst carrier is preferably to impregnate the catalyst carrier with the aqueous solution of the compound containing the hydrogenation active component. According to the preparation method of the hydrocracking catalyst provided by the present invention, there is no special limitation on the temperature of the impregnation, and it can be various temperatures that the impregnation liquid can reach. There is no special limitation on the time of impregnation, as long as the catalyst carrier can be loaded with the required amount of the compound containing the hydrogenation active component. For example, the conditions of the impregnation may include: the impregnation temperature is 5-150°C, and the impregnation time is 0.5-12 hours; in step S3, the conditions of the second drying treatment may include: the drying temperature is 50-300°C, preferably 105-250°C; the drying time is 1-24 hours, preferably 2-12 hours; the conditions of the second roasting may include: the roasting temperature is 350-600°C, preferably 400-550°C; the roasting time is 1-10 hours, preferably 2-8 hours.
[0058] According to the present invention, in step S1, the weight ratio of the pseudo-thin diatomite, the amorphous silicon aluminum oxide, the Y-type molecular sieve and the sesbania powder can be 10-80:20-85:1-20:1-5; preferably 15-75:25-80:2-15:2-4; the amount of the nitric acid solution can be 0.3-2.5 mL for every 100 g of the mixed powder; the SiO 2 The content of Fe can be less than 0.1wt%, 2 O 3 The content of Na 2 The content of O can be less than 0.15wt%, the content of water can be less than 3wt%, and the loss on ignition can be 32-38%; the pore volume of the pseudo-alumina can be 0.60-1.1mL / g, and the specific surface area can be 220-310m 2 / g; the characteristics of the amorphous silicon aluminum oxide may include: SiO 2 The content is 15-55%, Al 2 O 3 The content is 45-85%, and the bulk density is 250-450g / L; the mass concentration of the nitric acid solution can be: 0.5-2.5%.
[0059] According to conventional methods in the art, the preparation method of the hydrocracking catalyst provided by the present invention preferably also includes pre-sulfurization with sulfur, hydrogen sulfide or sulfur-containing raw materials at a temperature of 140-370°C in the presence of hydrogen before use. This pre-sulfurization can be carried out outside the vessel or in situ in the vessel to convert it into a sulfide type.
[0060] According to the present invention, the hydrogenation conditions may include: a temperature of 300-420°C, preferably 350-400°C; a hydrogen partial pressure of 3.5-20.0 MPa, preferably 5.0-15.0 MPa; a liquid hourly volume space velocity of the raw material of 0.1-5 h -1 , preferably 0.3-3.0h -1 .
[0061] The present invention is further illustrated by the following examples, but the present invention is not limited thereto. The specific surface area and pore volume of the porous support and catalyst were measured by the BET method according to the method specified in RIPP 151-90 on a six-station fully automatic specific surface and pore size distribution measuring instrument model Autosorb®-6B purchased from Quantachrome.
[0062] Example 1
[0063] Take ROCKET powder (from Catalyst Changling Branch, dry basis 64.5%) 100.78g, Siral40 powder (from Catalyst Changling Branch, produced by SASOL, silicon oxide content 40.0%, dry basis 79.7%) 40.15g, molecular sieve USY-A (from Catalyst Changling Co., Ltd., unit cell constant 24.56 Å, crystallinity 74.7%) 3.68; 3g sesbania powder, mix well for use. Add water to 1.3mL concentrated nitric acid to 72mL, and stir at room temperature for 5 minutes. Mix the nitric acid solution with the mixed powder, use a small extruder to repeatedly knead 3 times, and use a Ø1.6mm trilobal orifice plate to extrude the strips. The extruded strips are dried at 120℃ for 4.5 hours, and the dried strips are loaded into a roasting furnace and roasted at 570℃ for 3.6 hours. The air flow rate is maintained at 36L / h, and it is cooled to room temperature and taken out, which is recorded as carrier AC.
[0064] A mixed aqueous solution of nickel nitrate and ammonium metatungstate (obtained from Changling Catalyst Factory) was prepared according to the content of tungsten oxide in the catalyst being 15% by weight and nickel oxide being 3% by weight, and the amount of water was adjusted, and the prepared porous carrier was impregnated by the pore saturation method. The impregnated porous carrier was dried at 115°C for 5 hours, and then calcined at 440°C for 3 hours. During the calcination process, the air flow rate was maintained at not less than 15 cubic meters / (kg carrier•hour), thereby obtaining catalyst AS.
[0065] Example 2
[0066] Take ROCKET powder (from Catalyst Changling Branch, dry basis 64.5%) 85.27g, Siral40 powder (from Catalyst Changling Branch, produced by SASOL, silicon oxide content 40.0%, dry basis 79.7%) 43.91g, molecular sieve USY-B (from Catalyst Changling Co., Ltd., unit cell constant 24.45Å, crystallinity 68.8%) 11.99; 3g sesbania powder, mix well and set aside. Add water to 2.1mL concentrated nitric acid to 74mL, and stir at room temperature for 5 minutes. Mix the nitric acid solution with the mixed powder, use a small extruder to repeatedly knead 3 times, and use a Ø1.6mm trilobal orifice plate to extrude the strips. The extruded strips are dried at 120℃ for 4.5 hours, and the dried strips are loaded into a calcining furnace and calcined at 630℃ for 2.4 hours. The air flow rate is maintained at 24L / h, and then cooled to room temperature and taken out, which is recorded as carrier BC.
[0067] A mixed aqueous solution of nickel nitrate and ammonium metatungstate (obtained from Changling Catalyst Factory) was prepared according to the content of tungsten oxide in the catalyst of 16.5% by weight and nickel oxide content of 4% by weight, and the amount of water was adjusted, and the prepared porous carrier was impregnated by pore saturation method. The impregnated porous carrier was dried at 115°C for 5 hours, and then calcined at 450°C for 3 hours. During the calcination process, the air flow rate was maintained at not less than 20 cubic meters / (kg carrier•hour), thereby obtaining catalyst BS.
[0068] Example 3
[0069] Take CE powder (from Catalyst Changling Branch, produced by SASOL, dry basis 74.0%) 60.81g, SA-A powder (from Zibo Qimao Catalyst Co., Ltd., silicon oxide content 37.0%, dry basis 82.3%) 65.01g, molecular sieve USY-C (from Catalyst Changling Co., Ltd., unit cell constant 24.35Å, crystallinity 62.6%) 1.76; 3g sesbania powder, mix well for use. Add water to 90mL of 1.1mL concentrated nitric acid and stir at room temperature for 5 minutes. Mix the nitric acid solution with the mixed powder, use a small extruder to repeatedly knead 3 times, and use a Ø1.6mm trilobal orifice plate to extrude the strips. The extruded strips are dried at 120℃ for 4.5 hours, and the dried strips are loaded into a roasting furnace and roasted at 590℃ for 3.2 hours. The air flow rate is maintained at 32L / h, and it is cooled to room temperature and taken out, which is recorded as carrier CC.
[0070] A mixed aqueous solution of nickel nitrate and ammonium metatungstate (obtained from Changling Catalyst Factory) was prepared according to the content of tungsten oxide in the catalyst being 18% by weight and nickel oxide being 6% by weight, and the amount of water was adjusted, and the prepared porous carrier was impregnated by the pore saturation method. The impregnated porous carrier was dried at 115°C for 5 hours, and then calcined at 445°C for 3 hours. During the calcination process, the air flow rate was maintained at not less than 30 cubic meters / (kg carrier•hour), thereby obtaining the catalyst CS.
[0071] Example 4
[0072] Take 47.30g of CE powder (obtained from Catalyst Changling Branch, produced by SASOL, dry basis 74.0%), 72.23g of SA-B powder (obtained from Zibo Qimao Catalyst Co., Ltd., silicon oxide content 31.0%, dry basis 80.3%), 8.39 molecular sieve USY-B (obtained from Catalyst Changling Co., Ltd., unit cell constant 24.45Å, crystallinity 68.8%), and 3g of field sesbania powder, mix well for use. Add water to 93mL of 1.9mL concentrated nitric acid and stir at room temperature for 5 minutes. Mix the nitric acid solution with the mixed powder, use a small extruder to repeatedly knead 3 times, and use a Ø1.6mm trilobal orifice plate to extrude the strips. The extruded strips are dried at 120℃ for 4.5 hours, and the dried strips are loaded into a roasting furnace and roasted at 610℃ for 2.8 hours. The air flow rate is maintained at 28L / h, and the strips are cooled to room temperature and taken out, which are recorded as carrier DC.
[0073] A mixed aqueous solution of nickel nitrate and ammonium metatungstate (obtained from Changling Catalyst Factory) was prepared according to the content of tungsten oxide in the catalyst of 21% by weight and nickel oxide content of 2% by weight, and the amount of water was adjusted, and the prepared porous carrier was impregnated by pore saturation method. The impregnated porous carrier was dried at 115°C for 5 hours, and then calcined at 440°C for 3 hours. During the calcination process, the air flow rate was maintained at not less than 10 cubic meters / (kg carrier•hour), thereby obtaining the catalyst DS.
[0074] Example 5
[0075] Take SB powder (from the catalyst Changling branch, produced by SASOL, dry basis 74.0%) 27.03g, Siral40 powder (from the catalyst Changling branch, produced by SASOL, silicon oxide content 40.0%, dry basis 79.7%) 94.10g, molecular sieve USY-B (from the catalyst Changling Co., Ltd., unit cell constant 24.45Å, crystallinity 68.8%) 6.00; 3g sesbania powder, mix well for use. Add water to 108mL of 1.5mL concentrated nitric acid and stir at room temperature for 5 minutes. Mix the nitric acid solution with the mixed powder, use a small extruder to repeatedly knead 3 times, and use a Ø1.6mm trilobal orifice plate to extrude the strips. The extruded strips are dried at 120℃ for 4.5 hours, and the dried strips are loaded into a roasting furnace and roasted at 620℃ for 2.6 hours. The air flow rate is maintained at 26L / h, and then cooled to room temperature and taken out, which is recorded as carrier FC.
[0076] A mixed aqueous solution of nickel nitrate and ammonium metatungstate (obtained from Changling Catalyst Factory) was prepared according to the content of tungsten oxide in the catalyst being 25% by weight and nickel oxide being 7% by weight, and the amount of water was adjusted, and the prepared porous carrier was impregnated by the pore saturation method. The impregnated porous carrier was dried at 115°C for 5 hours, and then calcined at 420°C for 3 hours. During the calcination process, the air flow rate was maintained at not less than 35 cubic meters / (kg carrier•hour), thereby obtaining the catalyst FS.
[0077] Comparative Example 1
[0078] Take 33.11g of USA powder (from Catalyst Changling Branch, produced by SASOL, dry basis 75.5%), 90.52g of SA-A powder (from Zibo Qimao Catalyst Co., Ltd., silicon oxide content 37.0%, dry basis 82.3%), 0.61 molecular sieve USY-A (from Catalyst Changling Co., Ltd., unit cell constant 24.56Å, crystallinity 74.7%), and 3g of field sesbania powder, mix well for use. Add water to 0.7mL of concentrated nitric acid to 107mL, and stir at room temperature for 5 minutes. Mix the nitric acid solution with the mixed powder, use a small extruder to repeatedly knead 3 times, and use a Ø1.6mm trilobal orifice plate to extrude the strips. The extruded strips are dried at 120℃ for 4.5 hours, and the dried strips are loaded into a roasting furnace and roasted at 600℃ for 3.0 hours. The air flow rate is maintained at 30L / h, and the strips are cooled to room temperature and taken out, which are recorded as carrier EC.
[0079] A mixed aqueous solution of nickel nitrate and ammonium metatungstate (obtained from Changling Catalyst Factory) was prepared according to the content of tungsten oxide in the catalyst being 23.5% by weight and nickel oxide being 3.5% by weight, and the amount of water was adjusted, and the prepared porous carrier was impregnated by the pore saturation method. The impregnated porous carrier was dried at 115°C for 5 hours, and then calcined at 425°C for 3 hours. During the calcination process, the air flow rate was maintained at not less than 17.5 cubic meters / (kg carrier•hour), thereby obtaining the catalyst ES.
[0080] Test Example 1
[0081] Catalysts were prepared by testing Examples 1-5 and Comparative Example 1, and the nickel content and tungsten content in each catalyst were tested based on the total amount of the catalyst and calculated as oxide; the carrier content based on the total mass of the hydrogenation catalyst; and the Y-type molecular sieve content based on the total mass of the carrier. The specific testing method was XRF, and the test results are shown in Table 1.
[0082] Table 1
[0083] Catalyst name Tungsten content / % Nickel content / % Carrier content / % Y-type molecular sieve content / % AS 15.00% 3.00% 82.00% 2.91% BS 16.50% 4.00% 79.50% 9.08% CS 18.00% 6.00% 76.00% 1.30% DS 21.00% 2.00% 77.00% 6.19% FS 25.00% 7.00% 68.00% 3.92% ES 23.50% 3.50% 73.00% 0.43%
[0084] Test Example 2
[0085] The one-pass process is adopted. The properties of the raw oil are diesel after liquid phase hydrogenation. DMDS and TPA are added to control the nitrogen content in the raw oil to 100ppm, the sulfur content to 2000ppm, and the density (20℃) to 0.8209g / cm 3 , refractive index (20℃) 1.4565; IBP 189℃; 30%, 236℃; 50%, 265℃; 90%, 336℃, freezing point, -12℃. After the catalyst is sulfurized by conventional methods, the hydrogen partial pressure is 13.0MPa and the space velocity is 2.0h -1, hydrogen to oil volume ratio is 1200. The reaction temperature is controlled at 340℃-390℃. The activity is measured by the reaction temperature required to achieve a given conversion rate. The higher the temperature, the lower the activity, and vice versa.
[0086] Table 2
[0087] Catalyst name Activity / ℃ Heavy naphtha selectivity at 20% conversion rate / % Heavy naphtha selectivity at 50% conversion rate / % Total heavy naphtha selectivity / % AS 385 76.1 68.2 144.3 BS 375 76.5 68.6 145.1 CS 396 75.2 67.3 142.5 DS 381 77.3 69.9 147.3 FS 385 75.3 67.3 142.6 ES 391 74.4 66.8 141.2
[0088] It can be seen from the data in Table 2 that, compared with the comparative example catalyst ES, the catalyst used in the embodiment of the present invention has higher selectivity for heavy naphtha at different conversion rates under similar activity. The sum of the heavy naphtha selectivity at two conversion rates is also better than that of the comparative agent.
[0089] The preferred embodiments of the present invention are described in detail above. However, the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, a variety of simple modifications can be made to the technical solution of the present invention, and these simple modifications all belong to the protection scope of the present invention.
[0090] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.
[0091] In addition, various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.
Claims
1. A method for hydrocracking diesel to produce more naphtha, characterized in that: Under hydrogenation conditions, diesel and hydrogen are contacted with a hydrogenation catalyst in a fixed bed hydrogenation reactor; the diesel is a paraffinic or paraffinic diesel fraction; Wherein, the hydrogenation catalyst comprises a carrier and an active metal component supported on the carrier; The active metal components are nickel and tungsten; based on the total amount of the catalyst and calculated as oxide, the nickel content is 0.5-10% by weight, and the tungsten content is 8-30% by weight; Based on the total mass of the hydrogenation catalyst, the content of the carrier is 65-85% by weight; The carrier contains a non-amorphous mesoporous acidic material and a Y-type molecular sieve; based on the total mass of the carrier, the content of the Y-type molecular sieve is 1.5-10% by weight; The coking diesel fraction in the diesel is within 10% by weight; the weight content of aromatics is not higher than 20%, the nitrogen content is not higher than 500 μg / g, the density is not greater than 0.88 g / mL; and the cetane index is not less than 40; The specific surface area of the carrier is 200-450m 2 / g; The hydrogenation catalyst is prepared according to the following steps: S1, mixing pseudo-thin aluminum water stone, amorphous silicon aluminum oxide, Y-type molecular sieve and sesbania powder to obtain a first mixed powder; mixing the first mixed powder with a nitric acid solution, kneading and extruding to obtain an extruded strip; performing a first drying and a first calcination on the extruded strip to obtain a carrier; S2, impregnating the support with an aqueous solution of a compound containing a nickel element and a compound containing a tungsten element to obtain an impregnated support; S3, performing a second drying and a second calcination on the impregnated support; In step S1, the weight ratio of the pseudo-thin aluminum hydroxide, the amorphous silicon aluminum oxide, the Y-type molecular sieve and the sesbania powder is 10-80:20-85:1-20:1-5; The characteristics of the amorphous silicon aluminum oxide include: a SiO2 content of 15-55%, an Al2O3 content of 45-85%, and a bulk density of 250-450 g / L.
2. The hydrocracking method according to claim 1, wherein: The initial distillation point of the diesel is 100-300°C; the final distillation point is 330-450°C.
3. The hydrocracking method according to claim 2, wherein: The initial distillation point of the diesel is 180-240°C; the final distillation point is 370-400°C.
4. The hydrocracking method according to claim 1, wherein: The nickel content is 1-8% by weight based on the total amount of the catalyst and calculated as oxide.
5. The hydrocracking method according to claim 4, wherein: Based on the total amount of the catalyst and calculated as oxide, the nickel content is 2-8% by weight, and the tungsten content is 20-28% by weight.
6. The hydrocracking method according to claim 1, wherein: Based on the total mass of the carrier, the content of the Y-type molecular sieve is 4-10% by weight; The unit cell constant of the Y-type molecular sieve is in the range of 2.42-2.465 nm.
7. The hydrocracking method according to claim 6, wherein: Based on the total mass of the carrier, the content of the Y-type molecular sieve is 6-10% by weight; The unit cell constant of the Y-type molecular sieve is in the range of 2.430-2.460 nm.
8. The hydrocracking method according to claim 1, wherein: The carrier has a porous structure; In the porous structure, the pores have a pore size in the range of 4-12 nm; The specific surface area of the carrier is 220-420m 2 / g; The pore volume of the carrier is 0.35-0.80 mL / g; The pore concentration value of the pores is not less than 0.
5.
9. The hydrocracking method according to claim 8, wherein: The possible pore diameter of the pores is in the range of 5-9 nm; The pore volume of the carrier is 0.40-0.75 mL / g; The pore concentration value of the pores is not less than 0.
75.
10. The hydrocracking method according to claim 1, wherein: The non-amorphous mesoporous acidic material is a silicon-aluminum composite oxide; In the non-amorphous mesoporous acidic material, the content of sodium oxide is less than 0.1 wt %.
11. The hydrocracking method according to claim 10, wherein: In the non-amorphous mesoporous acidic material, the content of sodium oxide is less than 0.01 wt %.
12. The hydrocracking method according to claim 11, wherein: In the non-amorphous mesoporous acidic material, the content of sodium oxide is less than 0.008 wt %.
13. The hydrocracking method according to claim 12, wherein: In the non-amorphous mesoporous acidic material, the content of sodium oxide is less than 0.005wt%.
14. The hydrocracking method according to claim 1, wherein: The compound containing nickel is selected from at least one of nickel nitrate, nickel sulfate, nickel acetate, basic nickel carbonate and nickel chloride; The compound containing tungsten element is selected from at least one of tungstic acid, tungstate and ethyl metatungstic acid.
15. The hydrocracking method according to claim 1, wherein: The compound containing tungsten is selected from at least one of metatungstic acid and metatungstate.
16. The hydrocracking method according to claim 1, wherein: In step S1, the mixing conditions include: temperature of 10-40°C, time of 1-10 minutes; the first drying conditions include: temperature of 80-350°C, time of 0.5-24 hours; the first calcination conditions include: temperature of 360-700°C, time of 0.2-12 hours, air flow of 20-50L / h; In step S2, the impregnation conditions include: an impregnation temperature of 5-150°C and an impregnation time of 0.5-12 hours; In step S3, the conditions of the second drying treatment include: drying temperature of 50-300°C; drying time of 1-24 hours; the conditions of the second calcination include: calcination temperature of 350-600°C; calcination time of 1-10 hours.
17. The hydrocracking method according to claim 16, wherein: In step S1, the first drying conditions include: temperature of 100-300°C; time of 1-12 hours; the first calcination conditions include: temperature of 400-650°C; time of 1-10 hours; In step S3, the conditions of the second drying treatment include: a drying temperature of 105-250°C; a drying time of 2-12 hours; the conditions of the second calcination include: a calcination temperature of 400-550°C; a calcination time of 2-8 hours.
18. The hydrocracking method according to claim 1, wherein: For every 100 g of the first mixed powder, the amount of the nitric acid solution is 0.3-2.5 mL; The content of SiO2 in the pseudo-thin diatomite is less than 0.1wt%, the content of Fe2O3 is less than 0.01wt%, the content of Na2O is less than 0.15wt%, the content of water is less than 3wt%, and the loss on ignition is 32-38%; the pore volume of the pseudo-thin diatomite is 0.60-1.1mL / g, and the specific surface area is 220-310m 2 / g; The mass concentration of the nitric acid solution is 0.5-2.5%.
19. The hydrocracking method according to claim 1, wherein: The weight ratio of the pseudo-thin alumina, the amorphous silicon aluminum oxide, the Y-type molecular sieve and the sesbania powder is 15-75:25-80:2-15:2-4.
20. The hydrocracking method according to claim 1, wherein: The hydrogenation conditions include: temperature of 300-420°C; hydrogen partial pressure of 3.5-20.0 MPa; liquid hourly volume space velocity of diesel feedstock of 0.1-5 h -1 .
21. The hydrocracking method according to claim 20, wherein: The hydrogenation conditions include: temperature of 350-400°C; hydrogen partial pressure of 5.0-15.0 MPa; liquid hourly volume space velocity of diesel feedstock of 0.3-3.0 h -1 .
Citation Information
Patent Citations
Hydrocracking catalyst and preparation method thereof
CN102463131B
Method for producing naphtha and clean gasoline by catalytic cracking diesel oil
CN105694966A
Hydrocracking catalyst and preparation method thereof
CN105709798A
Productive naphtha type hydrocracking catalyst and preparation method thereof
CN105817259A
Hydrocracking method capable of producing heavy naphtha and tail oil
CN107987879A